My ex-life [compact disc, unabridged] - McCauley, Stephen (Macmillan Audio, 2018)
David Hedges's life is coming apart at the seams. His job helping San Francisco rich kids get into the colleges of their parents choice is exasperating; his younger boyfriend has left him; and the beloved carriage house he rents is being sold. The last person he expects to hear from is Julie Fiske. It's been decades since they've spoken, and he's relieved to hear she's recovered from her brief, misguided first marriage. To him.